Ensino de eletrodinâmica por meio da pedagogia histórico-crítica: potencialidades do tema gerador cidades inteligentes - Silva, Bruno Reinaldo da (2021)
The present investigation is based on problems, pointed out in the literature and also from observations of the teacher/researcher, associated with the teaching of Electrodynamics in high school. This teaching is reduced to mathematical formalisms without association with the student's daily life. The importance of providing a study associated with the experiential world of the student is due to the fact that the knowledge close to the reality of the student becomes more significant. And, consequently, it allows him to be an active and active being in the reality he is in, confronting common sense with scientific knowledge. In view of this and verifying the potentialities of the intelligent cities generating theme, the following question was elaborated: What possibilities does the theme intelligent cities open for the teaching of electrodynamics? To answer this question, we sought subsidies in the Theory of Historical-Critical Pedagogy of Saviani (1999) and Gasparin (2015) and as support for the STEM approach. Based on these choices, the objective of the study was to analyze the potentialities of a didactic sequence of teaching of Electrodynamics in a context of Intelligent Cities. This proposal is an educational product in the form of a didactic sequence supported on the steps of Historical-Critical Pedagogy (Initial Social Practice, Problematization, Instrumentalization and Catharsis and Final Social Practice). Research takes a qualitative, action and participant approach, which was collected through the logbook, the materials produced by the students, the recorded classes of the discipline and the report of the kahoot gamified platform. In this context, the steps proposed by the Historical-Critical Pedagogy were used as categories of analyses. The results discussed in these categories indicate that a contextualized approach close to the students' daily lives contributes to a more significant learning of the concepts of Electrodynamics. Especially when the student puts himself in the place of a resident of a Smart City and has the possibility to contribute with intelligent solutions. It was also found that the steps proposed by the Historical-Critical Pedagogy provide subsidies for students to be active beings and active in the reality that they are, because the contents studied in the classroom make sense to them and present possibilities of how they can use this knowledge in their daily life. The didactic proposal was flexible and can be applied in a face-to-face and/or remote environment. Based on the data obtained, it can be concluded that the theme generating Intelligent Cities for the study of Electrodynamics provided a significant learning of the concepts of Electrodynamics. And that through the dimensions worked, according to the theory of Historical-Critical Pedagogy, it is possible to verify the greatest interests of students at a given time and work with them to provide quality teaching, meaningful learning and at the same time transformative. The educational product, in the form of a didactic sequence, that accompanies the study is available in the form of support material for basic education teachers on the program's website and on the eduCapes Portal <http://educapes.capes.gov.br/handle/capes/603303>.